Analisis Penyusunan Draf Panduan Praktik Klinis Pelayanan Radiologi di RRSUD Ajibarang Kabupaten Banyumas - Asri Indah Aryani; Sutopo Patria Jati; Tjahjono Kuntjoro (Jurnal Manajemen Kesehatan Indonesia, 2016)
A clinical practice guideline is a procedure implemented by group of a profession referred to National Guideline of Medical Service made by organisation of profession and approved by Director of a hospital. In providing health services to patients, radiology service must refer to the clinical practice guideline that is available in its service. The aim of this study was to explain the process of draft arrangement of the clinical practice guideline of radiology service at Ajibarang Public Hospital in Banyumas District. This was qualitative research aimed at investigating the arrangement process of the clinical practice guideline of radiology service collected from various sources and informants at Ajibarang Public Hospital in Banyumas District. Data were collected using methods of indepth interview, observation, and literature review, analysed using content analysis, and presented descriptively combined with matrix of interview results. In addition, data presentation was supported by results of field observation and literature review. The results of this research showed that viewed from aspects of resources, there were any barriers as follows: radiologist did not involve in the arrangement process and there was lack of communication between radiographer and an arrangement team of the clinical practice guideline of hospital. On the other hand, there was no barrier in the aspect of tariff pattern. Tariff of INA- CBGs have been used in a program of National Health Insurance and implemented since 1 January 2014. In the aspect of evidence availability, arranged clinical practice guideline was based on literature and textbook. A format of arranged clinical practice guideline draft consisted of title of action procedure, definition, indication, contra-indication, preparation, action procedure, post action procedure, levels of evidence, levels of recommendation, reviewers, indicators of action procedure of radiographer, and references. In conclusion, the arrangement process of the clinical practice guideline had been well implemented. However, radiologist had not involved. Director’s decree about arrangement team of the clinical practice guideline at Ajibarang Public Hospital needs to be revised. Radiology service needs to accomplish and determine final draft of the clinical practice guideline.